English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

natural log maybe?

2007-05-16 22:16:01 · 5 answers · asked by markdosdourian 1 in Science & Mathematics Mathematics

5 answers

e^(x+3)=10
ln(e^(x+3))=ln(10)
x+3=ln(10)
x=ln(10)-3

2007-05-16 22:18:48 · answer #1 · answered by electric 3 · 1 0

e^(x+3) = 10
ln e^(x+3) = ln 10
x + 3 = ln 10
x = ln 10 - 3

2007-05-16 22:31:47 · answer #2 · answered by anakind 1 · 0 0

e^(x+3)=10
ln e^(x+3)= ln 10
(x + 3) ln e = ln 10
x + 3 = ln 10
x = -3 + ln 10

2007-05-16 22:20:19 · answer #3 · answered by Mathematica 7 · 1 0

ln refers to log base e (natural log)
Take ln of both sides:-
x + 3 = ln 10
x = 2.3 - 3
x = - 0.7

2007-05-16 22:51:01 · answer #4 · answered by Como 7 · 0 0

truly it is solved by using natural logarythm.
ln : natural log
ln [ e^(x + 3) ] = ln10
x + 3 = 2,3 so x = 2,3 - 3 = -0,7
as a result.

2007-05-16 23:44:20 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers